Application of Quality Analysis Method to Identify the Best Interaction Style of Parent Companies and Their Subsidiaries (International Journal of Applied Research in Management and Economics, 2018)
Identifying the effective factors in improving project performance is one of the most important issues that researchers in the field of a project management deal with it. It is especially important in project-oriented organizations, which have a more complex value chain. Accordingly, with the goal of helping and better influencing the parent organizations on their own projects and creating value for them, design of the optimal style of interaction of the project-oriented parent organizations with subsets using the results of data qualitative content analysis was done by the authors of this paper in order to guide the researchers of this field toward the mentioned direction and conducting the field and case studies. In order to achieve the mentioned optimal style, first of all, the capabilities of the project-oriented parent organizations must be identified with a suitable approach and categorized in a coherent system that forms the organizational capability dimensions and taken action to formulate the optimized style based on the findings and achievements. While, this paper is the first scientific documentation of the Ph.D. thesis of the research team of the authors of this article, it addresses and invites other researchers and enthusiasts of this field to address the issue in various statistical societies.